The Invisible Employee: Success and Fragility of Automating Interlibrary Loan. Issue 3 (15th May 2017) - Schmidt, LeEtta M.
ABSTRACT: Libraries and their interlibrary loan departments have enacted different methods for improving processes and services to create greater efficiency and less waste. Techniques range from holistic, and expansive process improvement projects to leveraging the ability of request management systems to automate processes and services successfully. This article explores the effect of automation on the output of a sample interlibrary loan department and points out possible challenges that this automation success may create in the future.